Community Driven Development and Accountable Local Governance : Some Lessons from the Philippines - World Bank (Washington, DC, 2013)
This study evaluates the connections between community-driven development (CDD) and decentralized local governance, and the need to identify strategies for operational integration. It aims to deepen the understanding of how the institutional environment for local governance interacts with CDD project operations. It gives special emphasis on the issue of accountability, analyzing how CDD operations perform in terms of strengthening the capacity of citizens and civil society to hold local authorities and public service providers accountable, and the capacity of the local government to be held accountable. The study utilizes a two-pronged approach. First, it assesses the institutional environment for accountability in local governance. Second, it examines the operations of two major World Bank-assisted CDD projects in two municipal case study sites. Given that CDD projects both shape and are shaped by local governance contexts in which they are embedded, the study investigates how CDD operations in the Philippines are affected by and are helping reform local governance conditions. It is from the analysis of this interface between CDD operations and local governance conditions that the study aims to generate policy and operational recommendations to enhance integration between CDD and local governance approaches. The analysis of the institutional environment for accountability in local governance often found an enabling policy and legal framework in principle, but severely limiting constraints in practice.